10 years TRY: On-going developments, challenges & perspectives - Kattge, Jens (2017)
The TRY initiative (www.try-db.org) has started in February 2007 as outcome of the IGBP Fast Track Initiative on Refining Plant Functional Classifications with the expectation to help generate reliable predictions of how vegetation boundaries and ecosystem properties shift with climate and land-use changes? (Nature, July 2011). Thanks to continuous support by the ecological community and funding by the Max Planck Institute for Biogeochemistry, we are now able to review 10 years of history, point out on-going developments and discuss future challenges and perspectives of the TRY initiative. I would therefore like to take this opportunity and ask for feedback on which aspects of TRY should be improved to better serve the community in quantifying and understanding trait relationships to plant and ecosystem function.